Thermo-responsive rheological behavior of borinic acid polymer in dilute solution. Issue 86 (2nd September 2016) - Sun, X. L.; Liu, D. M.; Lv, X. H.; Zhou, P.; Sun, M.; Wan, W. M.
Abstract : Borinic acid polymer is rheologically thermo-responsive in solution, which expands its application as a new type of "smart" polymer. Abstract : In comparison with other boron containing polymers, the investigations on the borinic acid containing polymers have been mostly ignored in spite of their easy synthesis. Our previous studies indicate a borinic acid polymer (PBA) holds promising potential as a new type of stimuli-responsive polymer. However, the property investigations were mainly based on turbidity changes. Here, we report the rheological property investigations of PBA solution. The PBA dilute solution (0.1 wt%) in DMSO exhibits a relatively high modulus ( G ′ of ∼60 Pa and G ′′ of ∼15 Pa) at the frequency of 1 rad s −1 at 25 °C. Temperature dependent rheology results reveal the thermo-responsive rheological behavior of the PBA dilute solution. Mechanism investigations indicate the coil–microgel transition of the PBA chains plays important roles in the thermo-responsive rheological behavior of the PBA dilute solution. This work therefore extends the field of thermo-responsive polymeric materials and opens up a new avenue in the applications of borinic acid containing polymers, where thermo-responsive rheology changes play an important role.